In Praise of Heteronomy : Making Room for Revelation - Westphal, Merold (Indiana series in the philosophy of religion., 2017)
Recognizing the essential heteronomy of postmodern philosophy of religion, Merold Westphal argues against the assumption that human reason is universal, neutral, and devoid of presupposition. Instead, Westphal contends that any philosophy is a matter of faith and the philosophical encounter with theology arises from the very act of thinking. Relying on the work of Spinoza, Kant, and Hegel, Westphal discovers that their theologies render them mutually incompatible and their claims to be the voice of autonomous and universal reason look dubious. Westphal grapples with this plural nature of human thought in the philosophy of religion and he forwards the idea that any appeal to the divine must rest on a historical and phenomenological analysis.